Effectiveness of a Sifufbads Apprentice Module on SME Companies in Malaysia: A Case Study on Sifufbads Apprentice Student A Discourse from Islamic Perspectives - Bahari, Jamaluddin; Badariah Jemain, Siti; Hehsan, Aminuddin; Khairul Nizam Zainan Nazri, Mohd; Mat Ishak, Mardiana (International Journal of Psychosocial Rehabilitation, 2020)
The main challenge currently faced by many SME’s in Malaysia is the static sales. However, a strategic training module in the market could be a contributing factor to the weakness. The Sifufbads Apprentice Module (SAM) provides Sifufbads Apprentice Students (SAS) with a structured educational experience related to accelerating apprentice static sales on a single digital branding topic. This study investigates the effectiveness of the Sifufbads apprentice module on SME companies in Malaysia in prompting three different areas, namely USP, value, and presentation. The SAM Thinking Frame guides Sifubads Apprentice Students thinking, makes them aware of their ideas, and prompts them to revise their ideas considering sales via digital branding knowledge. We examined the Sifufbads Apprentice Students ideas about USP, Value and Presentation solutions before and after participating in the Sifufbads Apprentice Module to determine the extent to which the apprentice students' refined ideas: (1) were consistent with the collected training module throughout the module; (2) were drastically increasing sales; and (3) had progressed toward more sales ideas compared with their initial ideas (4) formula and strategy as preparation close high sales; and (5) Integration of platform marketing of online branding. The results indicate that the module was particularly effective for encouraging SME’s to revise their ideas about static sales solutions such that their ideas were consistent with sales data and Islamic point of view in order to achieve incredible increment in sales by years.